Steel slag-shale ceramsite composite material and preparation method thereof

By introducing shale ceramics into steel slag-shale ceramics composites, the steel slag-shale ceramics composites are developed, which solves the problems of slow hydration reaction, high density and poor thermal insulation performance of steel slag, and realizes the lightweight and efficient materials Thermal insulation effect.

CN119430823APending Publication Date: 2025-02-14GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821977.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the reuse process of steel slag, there are problems such as slow hydration reaction, large material system density and poor thermal insulation performance.

Method used

By introducing shale ceramics, a steel slag-shale ceramic composite material is developed, which includes steel slag micro powder, shale ceramics, machined sand and water, which is pressed by a hydraulic brick press and accelerated carbonization and water maintenance.

Benefits of technology

The lightweight design of the material system has been realized, which significantly improves the thermal insulation performance of the composite material, reduces the thermal conductivity by more than 40%, and reduces the apparent density by more than 30%. At the same time, the hydration process of steel slag is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430823A_ABST
    Figure CN119430823A_ABST
Patent Text Reader

Abstract

The invention provides a steel slag-shale ceramsite composite material and a preparation method thereof. According to the invention, by introducing shale ceramsite, the lightweight design of a material system is realized, and the self weight of the structure is effectively reduced; the excellent pore structure characteristic of the shale ceramsite is utilized, so that the heat preservation and insulation performance of the composite material is remarkably improved; compared with a steel slag-machine-made sand composite material in a control group, the heat conductivity coefficient of the steel slag-shale ceramsite composite material can be reduced by 40% or above, and the apparent density can be reduced by 30% or above; on the premise of ensuring the mechanical properties of the material, the hydration process of the steel slag is optimized by adopting a carbonization enhancement technology. Generally speaking, the preparation method of the steel slag-shale ceramsite composite material provided by the invention not only provides a new way for high-value utilization of the steel slag, but also has important practical significance in the aspects of energy conservation and emission reduction of buildings. Through multifunctional collaborative design, comprehensive improvement of material performance is achieved, and a solution with reference value is provided for development of green building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials and solid waste utilization, and in particular to a steel slag-shale ceramsite composite material and a preparation method thereof. Background Art

[0002] Steel slag is an industrial solid waste produced in the production of crude steel, accounting for about 10% to 15% of crude steel production. my country is the world's largest steel producer, but the comprehensive utilization rate of steel slag is far lower than that of developed countries. Since steel slag has hydration-active mineral phases such as tricalcium silicate and dicalcium silicate similar to cement, and has good carbonization activity, using it as a cement substitute or auxiliary cementitious material for concrete will become one of the ways to utilize steel slag resources. However, due to the main component C in steel slag, 2 S and C 3 S crystallizes during the slow cooling process, resulting in low hydration activity of steel slag, which restricts its development and application as a building material.

[0003] Since steel slag is currently one of the main solid wastes in the steel industry, there are typical problems in its recycling process, such as slow hydration reaction, high density of the material system, and poor thermal insulation performance. It is necessary to improve this. Summary of the invention

[0004] The present invention aims to provide a production process that solves the multiple challenges faced by traditional steel slag-based building materials during their application. As one of the main solid wastes in the steel industry, steel slag has typical problems such as slow hydration reaction, high density of the material system, and poor thermal insulation performance during its reuse. In order to overcome the above-mentioned challenges, the present invention proposes to develop a steel slag-shale ceramsite composite material and a preparation method thereof through the synergistic effect of shale ceramsite.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a steel slag-shale ceramsite composite material, comprising the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0007] The mass of the shale ceramsite is 0.1% to 100% of the mass of the machine-made sand.

[0008] Preferably, the mass ratio of water to steel slag powder is (0.1-0.3):1;

[0009] The mass ratio of the machine-made sand to the steel slag powder is (1-3):1.

[0010] Preferably, the steel slag powder comprises the following components in mass fractions: 40% to 50% calcium oxide, 4% to 9% magnesium oxide, 17% to 22% silicon dioxide, 5% to 10% aluminum oxide, and 12% to 20% iron oxide.

[0011] Preferably, the shale ceramsite comprises the following components in mass fractions: 2% to 5% calcium oxide, 0.5% to 2% magnesium oxide, 60% to 70% silicon dioxide, 15% to 25% aluminum oxide, and 5% to 10% iron oxide.

[0012] Preferably, the particle size of the shale ceramsite oxide is less than or equal to 5 mm;

[0013] The mesh number of the steel slag fine powder is 80 mesh to 800 mesh.

[0014] Preferably, the fineness modulus of the machine-made sand is 2.8-2.9, the grading category is Class I, and the grading zone is Zone 2.

[0015] In a second aspect, the present invention further provides a method for preparing the steel slag-shale ceramsite composite material, comprising the following steps:

[0016] S1, mixing steel slag powder, shale ceramsite, machine-made sand and water to obtain a steel slag-shale ceramsite composite slurry;

[0017] S2, pressing the steel slag-shale ceramsite composite slurry through a hydraulic brick-making machine to obtain a formed block;

[0018] S3, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor, and then subjected to water curing to obtain a steel slag-shale ceramsite composite material.

[0019] Preferably, the pressing pressure is 6-10 MPa, and the pressing time is maintained for not less than 30 seconds.

[0020] Preferably, the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3~0.4MPa, CO 2 The volume concentration is 90% to 100%, the temperature is 20℃-35℃, the relative humidity is 50%-70%, and the curing time is 0 to 8h.

[0021] Preferably, the water curing conditions are: curing in a saturated calcium hydroxide solution at a temperature of 20° C. to 35° C. for 0 to 28 days.

[0022] The steel slag-shale ceramsite composite material and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0023] The steel slag-shale ceramsite composite material of the present invention realizes the lightweight design of the material system through the introduction of shale ceramsite, effectively reducing the deadweight of the structure; utilizing the excellent pore structure characteristics of shale ceramsite, significantly improving the thermal insulation performance of the composite material; compared with the steel slag-machine-made sand composite material in the control group, the thermal conductivity of the steel slag-shale ceramsite composite material can be reduced by more than 40%, and the apparent density can be reduced by more than 30%; under the premise of ensuring the mechanical properties of the material, the carbonization enhancement technology is adopted to optimize the hydration process of the steel slag. In summary, the preparation method of the steel slag-shale ceramsite composite material of the present invention not only provides a new way for the high-value utilization of steel slag, but also has important practical significance in terms of energy conservation and emission reduction in buildings. Through multifunctional collaborative design, the comprehensive improvement of material performance is achieved, providing a solution with reference value for the development of green building materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 The compressive strength and thermal conductivity test results of composite materials A1, A2, A3, and R were obtained by the methods of Examples 1 to 2 and Comparative Examples 1 to 2, respectively;

[0026] Figure 2 The apparent density test results of composite materials A1, A2, A3, and R were obtained by the methods of Examples 1 to 2 and Comparative Examples 1 to 2, respectively;

[0027] Figure 3 The compressive strength test results of composite materials B1, B2, B3 and RB were obtained by the methods of Examples 3 to 4 and Comparative Examples 3 to 4, respectively. DETAILED DESCRIPTION

[0028] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0031] The embodiment of the present application provides a steel slag-shale ceramsite composite material, which includes the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water; the mass of the shale ceramsite is 0.1% to 100% of the mass of the machine-made sand.

[0032] In some embodiments, the mass ratio of water to steel slag powder is (0.1-0.3):1, and the mass ratio of machine-made sand to steel slag powder is (1-3):1; steel slag powder is used as a cementitious material; the water-binder ratio is 0.10-0.30, and the sand-binder ratio is 1-3; shale expanded clay replaces machine-made sand at a ratio of 0.1% to 100%.

[0033] The steel slag-shale ceramsite composite material of the present invention comprises steel slag powder and shale ceramsite; shale ceramsite is an inorganic porous material with low bulk density, high porosity, good chemical stability and thermal stability. When it is compounded with a steel slag-based cementitious system and applied to enclosure components such as functional wall panels and building blocks, it can not only significantly reduce the deadweight of the structure, but also exhibit excellent thermal insulation performance due to its unique porous structure and low thermal conductivity. Therefore, this type of new composite building material has broad application prospects and important engineering value in the field of energy-saving buildings. Steel slag is used as a cementitious material to replace traditional cement, and CO 2The rapid carbonization reaction mechanism can significantly improve the comprehensive performance of the steel slag-shale ceramsite composite material system. This composite system not only shows excellence in building energy saving, thermal insulation performance optimization and structural lightweight, but also meets the multi-dimensional technical requirements of green buildings for enclosure materials. From the perspective of engineering application, this provides important reference value for green buildings that have strict control requirements on building thermal insulation performance and structural deadweight. At the same time, this resource utilization model has important practical significance and demonstration value for the steel industry to achieve the "dual carbon" goal, promote industrial transformation and upgrading, and promote sustainable development.

[0034] Furthermore, the shale ceramsite used in the present invention is a lightweight fine aggregate. From the microscopic structure point of view, the shale ceramsite has a large number of microporous structures inside, and this porous characteristic significantly reduces its volume density. At the same time, it also exhibits significant comprehensive properties such as thermal insulation, antifreeze and earthquake resistance. Although replacing traditional sand with shale ceramsite will lead to a decrease in the compressive strength of the composite material to a certain extent, studies have shown that through the optimization of the carbonization curing process and the scientific and reasonable ratio design, it is possible to not only effectively reduce the density of the product, but also ensure that its compressive performance is maintained within the specified standard range. This discovery fully demonstrates the application potential of shale ceramsite in the modification of building materials, and provides an important theoretical basis and practical guidance for the development of new building energy-saving materials.

[0035] When the shale ceramsite replacement rate reaches 100%, the compressive strength of the steel slag-shale ceramsite composite material decreases by 40% compared with the steel slag-machine-made sand composite material. However, when the shale ceramsite replacement rate is 30%, the strength and density requirements of the MU20 block in the Chinese standard GB50003-2011 of the steel slag-shale ceramsite composite material are met, and its thermal insulation performance is significant. Due to the surface characteristics and inherent micropores of shale ceramsite, their distribution in the mixture will lead to a reduction in the contact surface between the original materials and increase the porosity in the mixed system. These additional voids increase, resulting in a longer heat conduction path, thereby reducing the thermal conductivity of the product. At the same time, due to these voids, CO is promoted 2 The transfer in the material allows the carbonization process to proceed rapidly, allowing the product to reach a certain standard of compressive strength requirements in a short period of time.

[0036] In some embodiments, steel slag powder is used as the main cementitious material of the block, and its mesh size is 80-800 mesh, and the specific surface area is about 306.6m 2 / kg; the steel slag powder includes the following components in mass fraction: 40% to 50% calcium oxide, 4% to 9% magnesium oxide, 17% to 22% silicon dioxide, 5% to 10% aluminum oxide, and 12% to 20% iron oxide.

[0037] In some embodiments, shale ceramsite, a lightweight porous particle containing partially carbonized active oxides, is used to replace machine-made sand; the shale ceramsite includes the following components in mass fractions: 2% to 5% calcium oxide, 0.5% to 2% magnesium oxide, 60% to 70% silicon dioxide, 15% to 25% aluminum oxide, and 5% to 10% iron oxide.

[0038] In some embodiments, the bulk density of shale ceramsite is about 580 kg / m 3 The cylinder pressure strength is about 2.9MPa, and the 3h water absorption rate is about 8.4%.

[0039] In some embodiments, the shale ceramsite should be screened, cleaned, and dried first, and the particle size should be less than or equal to 5 mm.

[0040] In some embodiments, the ratio of shale ceramsite to machine-made sand is 0.1% to 100%, more preferably 30% to 50%. That is, the mass of shale ceramsite is 0.1% to 100%, more preferably 30% to 50% of the mass of machine-made sand.

[0041] In some embodiments, the machine-made sand has a fineness modulus of 2.8 to 2.9, preferably 2.86, and meets the Chinese standard GB / T14684-2011, which is Class I and has a grading zone of Zone 2.

[0042] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned steel slag-shale ceramsite composite material, comprising the following steps:

[0043] S1, mixing steel slag powder, shale ceramsite, machine-made sand and water to obtain a steel slag-shale ceramsite composite slurry;

[0044] S2, pressing the steel slag-shale ceramsite composite slurry through a hydraulic brick-making machine to obtain a formed block;

[0045] S3, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor, and then subjected to water curing to obtain a steel slag-shale ceramsite composite material.

[0046] In some embodiments, the pressing pressure is 6-10 MPa, more preferably 8 MPa, and the pressing time is maintained for no less than 30 seconds.

[0047] In some embodiments, the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3~0.4MPa, CO 2 The volume concentration is 90% to 100%, the temperature is 20℃-35℃, the relative humidity is 50%-70%, and the curing time is 0 to 8h.

[0048] In some embodiments, the water curing conditions are: curing in a saturated calcium hydroxide solution at a temperature of 20° C. to 35° C. for 0 to 28 days.

[0049] In some embodiments, the accelerated carbonization curing time is 0 to 8 hours, more preferably 3 hours.

[0050] The shale ceramsite used in the present invention is a lightweight fine aggregate. From the microscopic structure point of view, the shale ceramsite has a large number of microporous structures inside, and this porous characteristic significantly reduces its volume density. At the same time, it also shows significant comprehensive properties such as thermal insulation, antifreeze and earthquake resistance. Although replacing traditional sand with shale ceramsite will lead to a decrease in the compressive strength of the composite material to a certain extent, studies have shown that through the optimization of the carbonization curing process and the scientific and reasonable ratio design, it is possible to not only effectively reduce the density of the product, but also ensure that its compressive performance is maintained within the specified standard range. This discovery fully demonstrates the application potential of shale ceramsite in the modification of building materials, and provides an important theoretical basis and practical guidance for the development of new building energy-saving materials.

[0051] Compared with ordinary steel slag-based blocks, the present invention has the following advantages:

[0052] (1) The introduction of shale ceramsite has achieved a lightweight design of the material system, effectively reducing the deadweight of the structure;

[0053] (2) The excellent pore structure characteristics of shale ceramsite significantly improve the thermal insulation performance of the composite material; compared with the steel slag-machine-made sand composite material in the control group, the thermal conductivity of the steel slag-shale ceramsite composite material can be reduced by more than 40%, and the apparent density can be reduced by more than 30%;

[0054] (3) While ensuring the mechanical properties of the material, the carbonization enhancement technology is used to optimize the hydration process of steel slag.

[0055] In summary, the preparation method of the steel slag-shale ceramsite composite material involved in the present invention not only provides a new way for the high-value utilization of steel slag, but also has important practical significance in building energy conservation and emission reduction. Through multifunctional collaborative design, the comprehensive improvement of material performance is achieved, providing a solution with reference value for the development of green building materials.

[0056] The steel slag-shale ceramsite composite material of the present application is further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means adopted in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0057] In the following examples, steel slag powder is used as the main cementitious material of the blocks, with an average mesh size of 150 meshes and a specific surface area of ​​306.6 m 2 / kg; Steel slag powder includes the following components by mass fraction: calcium oxide 50%, magnesium oxide 5%, silicon dioxide 20%, aluminum oxide 8%, and iron oxide 17%;

[0058] In the following examples, the bulk density of shale ceramsite is about 580 kg / m 3 The cylinder pressure strength is 2.9MPa, the water absorption rate is 8.4% in 3h, the particle size is 1mm, and the shale ceramsite includes the following components by mass fraction: 5% calcium oxide, 2% magnesium oxide, 65% silicon dioxide, 20% aluminum oxide, and 8% iron oxide.

[0059] In the following embodiments, the machine-made sand has a fineness modulus of 2.86, meets the gradation category of Class I and the gradation zone of Zone 2 of the Chinese standard GB / T 14684-2011.

[0060] Example 1

[0061] The embodiment of the present application provides a steel slag-shale ceramsite composite material, comprising the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0062] Wherein, 30 parts by weight of shale ceramsite and 70 parts by weight of machine-made sand are mixed to obtain a mixed material;

[0063] A steel slag-shale ceramsite composite material comprising 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water;

[0064] The preparation method of the above-mentioned steel slag-shale ceramsite composite material comprises the following steps:

[0065] S1. 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0066] S2, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor to obtain a steel slag-shale ceramsite composite material (denoted as A1);

[0067] Among them, the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27°C, and the curing time is 3h.

[0068] Example 2

[0069] The embodiment of the present application provides a steel slag-shale ceramsite composite material, comprising the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0070] Wherein, 50 parts by weight of shale ceramsite and 50 parts by weight of machine-made sand are mixed to obtain a mixed material;

[0071] A steel slag-shale ceramsite composite material comprising 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water;

[0072] The preparation method of the above-mentioned steel slag-shale ceramsite composite material comprises the following steps:

[0073] S1. 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0074] S2, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor to obtain a steel slag-shale ceramsite composite material (denoted as A2);

[0075] Among them, the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27°C, and the curing time is 3h.

[0076] Comparative Example 1

[0077] This comparative example provides a steel slag-shale ceramsite composite material, including the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0078] Wherein, 100 parts by weight of shale ceramsite and 0 parts by weight of machine-made sand are mixed to obtain a mixed material;

[0079] A steel slag-shale ceramsite composite material comprising 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water;

[0080] The preparation method of the above-mentioned steel slag-shale ceramsite composite material comprises the following steps:

[0081] S1. 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0082] S2, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor to obtain a steel slag-shale ceramsite composite material (denoted as A3);

[0083] Among them, the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27°C, and the curing time is 3h.

[0084] Comparative Example 2

[0085] This comparative example provides a steel slag-mechanical sand composite material, comprising the following raw materials: 100 parts by weight of steel slag powder, 200 parts by weight of mechanical sand and 12 parts by weight of water;

[0086] The method for preparing the steel slag composite material comprises the following steps:

[0087] S1. 100 parts by weight of steel slag powder, 200 parts by weight of machine-made sand and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0088] S2, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor to obtain a steel slag-machine-made sand composite material (denoted as R);

[0089] Among them, the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27°C, and the curing time is 3h.

[0090] Composite materials A1, A2, A3, and R were obtained according to the methods of Examples 1 to 2 and Comparative Examples 1 to 2, respectively. The composite materials were tested for compressive strength (reference standard GB / T 17671-2021), thermal conductivity (reference standard GB / T 10294), and apparent density (reference standard GB / T 4111-2013). The test results are shown in Figure 1-2 .

[0091] from Figures 1-2 It can be seen that the thermal conductivity of A1, A2, and A3 is reduced by 34.6%, 42.7%, and 49.3% respectively compared with R in comparative example 2; the compressive strength of R and A1, A2, and A3 in comparative example 2 is (rounded) 17MPa, 15MPa, 11MPa, and 9MPa respectively; the apparent density of R and A1, A2, and A3 in comparative example 2 is 2400kg / m 3 、1980kg / m 3 、1870kg / m3 、1650kg / m 3 .

[0092] Example 3

[0093] The embodiment of the present application provides a steel slag-shale ceramsite composite material, comprising the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0094] Wherein, 30 parts by weight of shale ceramsite and 70 parts by weight of machine-made sand are mixed to obtain a mixed material;

[0095] A steel slag-shale ceramsite composite material comprising 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water;

[0096] The preparation method of the above-mentioned steel slag-shale ceramsite composite material comprises the following steps:

[0097] S1. 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0098] S2. The formed blocks are subjected to accelerated carbonization curing in a carbonization reactor; wherein the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27℃, and the curing time is 3h;

[0099] S3. Carry out water curing on the blocks after carbonization curing in S2. The water curing conditions are: curing in a saturated calcium hydroxide solution at a temperature of 25° C. for 0 to 28 days (specific curing time is 0 days, 7 days, and 28 days) to obtain a steel slag-shale ceramsite composite material (recorded as B1).

[0100] Example 4

[0101] The embodiment of the present application provides a steel slag-shale ceramsite composite material, comprising the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0102] Wherein, 50 parts by weight of shale ceramsite and 50 parts by weight of machine-made sand are mixed to obtain a mixed material;

[0103] A steel slag-shale ceramsite composite material comprising 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water;

[0104] The preparation method of the above-mentioned steel slag-shale ceramsite composite material comprises the following steps:

[0105] S1. 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0106] S2. The formed blocks are subjected to accelerated carbonization curing in a carbonization reactor; wherein the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27℃, and the curing time is 3h;

[0107] S3. Carry out water curing on the blocks after carbonization curing in S2. The water curing conditions are: curing in a saturated calcium hydroxide solution at a temperature of 25° C. for 0 to 28 days (specific curing time is 0 days, 7 days, and 28 days) to obtain a steel slag-shale ceramsite composite material (recorded as B2).

[0108] Comparative Example 3

[0109] This comparative example provides a steel slag-shale ceramsite composite material, including the following raw materials: steel slag powder, shale ceramsite, machine-made sand and water;

[0110] Wherein, 100 parts by weight of shale ceramsite and 0 parts by weight of machine-made sand are mixed to obtain a mixed material;

[0111] A steel slag-shale ceramsite composite material comprising 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water;

[0112] The preparation method of the above-mentioned steel slag-shale ceramsite composite material comprises the following steps:

[0113] S1. 100 parts by weight of steel slag powder, 200 parts by weight of mixed materials and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0114] S2. The formed blocks are subjected to accelerated carbonization curing in a carbonization reactor; wherein the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27℃, and the curing time is 3h;

[0115] S3. The blocks after carbonization curing in S2 are water-cured under the following conditions: curing in a saturated calcium hydroxide solution at a temperature of 25° C. for 0 to 28 days (specific curing time is 0 days, 7 days, and 28 days) to obtain a steel slag-shale ceramsite composite material (denoted as B3).

[0116] Comparative Example 4

[0117] This comparative example provides a steel slag-mechanical sand composite material, comprising the following raw materials: 100 parts by weight of steel slag powder, 200 parts by weight of mechanical sand and 12 parts by weight of water;

[0118] The method for preparing the steel slag composite material comprises the following steps:

[0119] S1. 100 parts by weight of steel slag powder, 200 parts by weight of machine-made sand and 12 parts by weight of water are mixed and stirred evenly, and then placed in a rectangular parallelepiped mold with a length of 50 mm, a width of 50 mm and a height of 90 mm to form a building block; wherein the molding pressure is controlled at 8 MPa and the molding pressure time is 30 s;

[0120] S2. The formed blocks are subjected to accelerated carbonization curing in a carbonization reactor; wherein the accelerated carbonization curing conditions are: CO 2 The pressure is 0.3MPa, the volume concentration is 99.9%, the relative humidity is 65%, the temperature is 27℃, and the curing time is 3h;

[0121] S3. Carry out water curing on the blocks after carbonization curing in S2. The water curing conditions are: curing in a saturated calcium hydroxide solution at a temperature of 25° C. for 0 to 28 days (specific curing time is 0 days, 7 days, and 28 days) to obtain a steel slag-machine-made sand composite material (denoted as RB).

[0122] Composite materials B1, B2, B3, and RB were obtained according to the methods of Examples 3 to 4 and Comparative Examples 3 to 4, respectively. The compressive strength of the composite materials was tested (reference standard GB / T 17671-2021). The test results are shown in Figure 3 .

[0123] from Figure 3 It can be seen that the compressive strengths of RB, B1, B2 and B3 in Comparative Example 4 after 28 days of water curing are (rounded) 25MPa, 21MPa, 18MPa and 15MPa respectively.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A steel slag-shale ceramsite composite material, characterized in that: The raw materials include: steel slag powder, shale ceramsite, machine-made sand and water; The mass of the shale ceramsite is 0.1% to 100% of the mass of the machine-made sand.

2. The steel slag-shale ceramsite composite material according to claim 1, characterized in that: The mass ratio of water to steel slag powder is (0.1-0.3):1; The mass ratio of the machine-made sand to the steel slag powder is (1-3):

1.

3. The steel slag-shale ceramsite composite material according to claim 1, characterized in that: The steel slag powder comprises the following components in mass fractions: 40% to 50% calcium oxide, 4% to 9% magnesium oxide, 17% to 22% silicon dioxide, 5% to 10% aluminum oxide, and 12% to 20% iron oxide.

4. The steel slag-shale ceramsite composite material according to claim 1, characterized in that: The shale ceramsite comprises the following components in mass fractions: 2% to 5% of calcium oxide, 0.5% to 2% of magnesium oxide, 60% to 70% of silicon dioxide, 15% to 25% of aluminum oxide, and 5% to 10% of iron oxide.

5. The steel slag-shale ceramsite composite material according to claim 1, characterized in that: The particle size of the shale ceramsite oxide is less than or equal to 5 mm; The mesh number of the steel slag fine powder is 80 mesh to 800 mesh.

6. The steel slag-shale ceramsite composite material according to claim 1, characterized in that: The fineness modulus of the machine-made sand is 2.8-2.9, the grading category is Class I, and the grading zone is Zone 2.

7. A method for preparing the steel slag-shale ceramsite composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing steel slag powder, shale ceramsite, machine-made sand and water to obtain a steel slag-shale ceramsite composite slurry; S2, pressing the steel slag-shale ceramsite composite slurry through a hydraulic brick-making machine to obtain a formed block; S3, the formed blocks are subjected to accelerated carbonization curing in a carbonization reactor, and then subjected to water curing to obtain a steel slag-shale ceramsite composite material.

8. The method for preparing the steel slag-shale ceramsite composite material according to claim 7, characterized in that: The pressing pressure is 6-10 MPa, and the pressing time is maintained for no less than 30 seconds.

9. The method for preparing the steel slag-shale ceramsite composite material according to claim 7, characterized in that: The accelerated carbonization curing conditions are: CO2 pressure of 0.3-0.4MPa, CO2 volume concentration of 90%-100%, temperature of 20℃-35℃, relative humidity of 50%-70%, and curing time of 0-8h.

10. The method for preparing the steel slag-shale ceramsite composite material according to claim 7, characterized in that: The water curing conditions are: curing in a saturated calcium hydroxide solution at a temperature of 20°C to 35°C for 0 to 28 days.